Quantitative manoeuvring characteristics of an underwater vehicle equipped with collective and cyclic pitch propeller - Nguyen, HD; Dubois, A; Leong, ZQ; Binns, J; Tran, MQ (Bach Khoa Publishing House, 2018)
Operating an underwater vehicle at low speed, such as docking (homing), stationary keeping and under-icenavigation, in severe and harsh environments is a great challenge. Applications of underwater vehicles havebeen widened from small underwater/subsea missions to complicated under-ice missions such as in theArctic and Antarctic areas. To fulfil the complicated missions in such harsh environmental conditions, theconventional propulsion systems for underwater vehicles are not appropriate any more, thus operation ofsuch underwater vehicles requires new types of propulsion system to enhance efficiency, to prolongoperating time period and to effectively operate underwater vehicles at very low speed. A novel type ofpropulsion system, namely controllable and cyclic pitch propeller (CCPP), has been designed for underwatervehicles and its performance has been quantified by Computational Fluids Dynamics (CFD) simulation andtowing tank captive tests. The idea of a CCPP for an underwater vehicle comes from the rotor of ahelicopter. The current investigation shows a great potential of this type of propulsion system to be analternative propulsion system in order to improve omni-directional manoeuvring characteristics andcontrollability. This paper is to report on the latest information on quantification of the performance of theunderwater vehicle equipped with the CCPP using numerical and experimental approaches.